Pengaruh Dana Desa terhadap Peningkatan Kesejahteraan Masyarakat: Studi Kasus yang Berada di Kecamatan Telaga Jaya, Kabupaten Gorontalo - Aprilindah Uno, Sri; Noholo, Sahnim; Mahmud, Mulyani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to determine the effect of village funds on improving community welfare (case study of villages in telaga jaya). The research method used in this research is a quantitative method with data collection techniques using surfey questionnaires and observation. The number of respondents in this research was 50 respondents in all village officials in the telaga jaya, Gorontalo Regrency. The tool used in this research uses simple linier regression analysis. Based on the results of this research, it is known that the influence of village funds on improving community walfare has a positive and significant effect on increasing community walfare in villages in telaga jaya , Gorontalo Regrency.